2015
DOI: 10.1002/bjs.9816
|View full text |Cite
|
Sign up to set email alerts
|

Family history and outcome of young patients with breast cancer in the UK (POSH study)

Abstract: Background: Young patients presenting to surgical clinics with breast cancer are usually aware of their family history and frequently believe that a positive family history may adversely affect their prognosis. Tumour pathology and outcomes were compared in young British patients with breast cancer with and without a family history of breast cancer.Methods: Prospective Outcomes in Sporadic versus Hereditary breast cancer (POSH) is a large prospective cohort study of women aged less than 41 years with breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
(55 reference statements)
4
19
1
Order By: Relevance
“…In this age group malignant lesions are less common, difficult to detect and can more easily be interpreted as benign lesions. In the current study, 61% of the patients had negative family history of breast or ovarian cancer and 75.6% was symptomatic at diagnosis, which is consistent with other studies [9,10]. Our results showed that mammography can provide essential information on the diagnosis of breast cancer in women under 40 years.…”
Section: Discussionsupporting
confidence: 91%
“…In this age group malignant lesions are less common, difficult to detect and can more easily be interpreted as benign lesions. In the current study, 61% of the patients had negative family history of breast or ovarian cancer and 75.6% was symptomatic at diagnosis, which is consistent with other studies [9,10]. Our results showed that mammography can provide essential information on the diagnosis of breast cancer in women under 40 years.…”
Section: Discussionsupporting
confidence: 91%
“…In women aged < 35 or 40 years with a positive first-degree FH of breast or ovarian cancer, the positive FH was not associated with survival. 39,40 However, our present results have shown that a positive FH of breast, ovarian, pancreatic, and/or prostate cancer in…”
Section: Discussioncontrasting
confidence: 56%
“…With regard to disease‐free survival, recent findings from the UK Prospective Outcomes in Sporadic versus Hereditary breast cancer (POSH) suggested that there is no difference in disease progression between female BC patients with or without a family history, with a HR of 0.89 (95% CI: 0.76–1.03) . It is clinically relevant to know that women with a family history of BC are not necessarily at a greater risk.…”
Section: Discussionmentioning
confidence: 99%